Occult Basal Cell Carcinoma Arising in Seborrheic Keratosis - Yuichi Kurihara; Masutaka Furue (Karger Publishers, 2019)
Both seborrheic keratosis and basal cell carcinoma are common skin tumors in daily clinical practice. However, the coexistence of seborrheic keratosis and basal cell carcinoma is rare. In this report, we present a case of occult microscopic basal cell carcinoma arising in a lesion of seborrheic keratosis. This case indicates that the basal cell carcinoma could arise from seborrheic keratosis and might help to clarify the origin of basal cell carcinoma.